SELF-REGULATION & PERSOALAN ETIKA DALAM INDUSTRI PENYIARAN DI INDONESIA (Mendambakan Penyiaran Radio yang Beretika) - Budhi Widi Astuti (Universitas Kristen Satya Wacana, 2013)
Radio broadcasting industry developed rapidly after the reform due to the independent press. This is evidenced by the increasing number of radio stations that have been in operation and has an official permit, as well as the station requested permission to broadcast or radio stations that do not have official permission. Unfortunately, an increasing number of radio stations in quantity is not followed by an increase in quality, both in terms of broadcast content as well as the behavior of the perpetrators of these media broadcasting. Many ethical violations that negatively affect the public. This paper intends to assert the importance of regulation for radio broadcasters, both legislation and self-regulation in the form of regulations set by the Indonesian Broadcasting Commission (Komisi Penyiaran Indonesia). More deeply about the importance of understanding and applying ethics in radio broadcasting activities. Radio broadcasting not only has a function as a medium of information, education, wholesome entertainment, control and social cohesion, but also has the function of economy and culture. However, it does not mean eliminating one of the functions or the domination of one function only. Dilemma competition in the radio broadcasting industry is not expected to make the radio industry only producing broadcast content that interests only, but should also contain ethical values. Thus, the establishment of radio broadcasting that 'healthy' is not just a mere dream. Key words: Radio broadcasting, media regulations, self-regulation, ethics, broadcasting with ethics.